Parallel Universes? Alison Bechdel’s Dykes to Watch Out For (1983-2008) and Diane DiMassa’s Hothead Paisan: Homicidal Lesbian Terrorist (1991-1996) - Hélène Tison (Transatlantica)
Cartoonists Alison Bechdel and Diane DiMassa, writing in a socially and culturally heteronormative context, give life to a fantasy: worlds that, instead of excluding dykes from public space, are entirely organized around lesbian characters. Both reflect the debates within lesbian feminist groups, the tensions between lesbian and straight feminists, and the strategies that can be deployed in the face of discrimination. They create utopian (Bechdel) and dystopian (DiMassa) universes that parallel and question contemporary US realities. DiMassa presents a caricatured, degraded version of US society, focusing on its relation to minorities, as seen through the eyes of a “homicidal lesbian terrorist” intent on reclaiming their right to exist in the world. Bechdel’s syndicated bi-monthly strip is a twenty-five-year running commentary on US politics viewed from a lesbian perspective, that also discusses such feminist and/or LGBTQ+ issues as gender relations, the sodomy laws, trans rights, marriage equality, etc., and that shows her characters evolving on a number of these issues, as many Americans have since the 1980s. For all their provocation and humor, these comics from the margins have remained eerily topical.